Representing improved tropospheric ozone distribution over the Northern Hemisphere by including lightning NOx emissions in CHIMERE - S. Ghosh; A. Cholakian; S. Mailler; S. Mailler; L. Menut (Atmospheric Chemistry and Physics)
Estimating nitrogen oxide emissions from lightning (LNOx) in models is highly uncertain, affecting the accuracy of atmospheric composition and air quality assessments. Still, it is essential to include these emissions in models to increase the realism of representing the gases and aerosols. LNOx emissions have recently been incorporated into the updated version of the CHIMERE model (v2023r2). In this study, we evaluate the present state of modelling the lightning flashes over the Northern Hemisphere (NH), using a classical scheme based on cloud-top height (CTH) and an updated ice-flux-based scheme (ICEFLUX). We conduct a comprehensive 3D comparison of model outputs, including in situ measurements and satellite data, to rigorously assess the robustness and applicability of these parameterizations. The comparative analysis reveals that the CTH scheme provides a more accurate spatial variability of lightning flashes over lands and tropical oceans. Both parameterizations accurately capture the magnitude of lightning flashes over the tropics, while the ICEFLUX scheme is more effective in representing mid-latitudinal flashes. However, both schemes perform well in capturing the seasonal variation of lightning flashes. The estimated flash frequencies over the NH from the experiments closely align with satellite observations, and the LNOx emissions fall within the range reported in previous modelling studies. There is an overall increase in ozone (O3) concentration due to inclusion of LNOx, which substantially improves the tropospheric O3 distribution, specifically in the tropical free troposphere. The LNOx emissions hence critically influence the O3 burden as well as the hydroxyl radicals, which further impact the atmospheric lifetime of trace gas methane.